NF-κ B mediates the effect of glucosylceramide synthase on P-glycoprotein modulation in a drug-resistance leukemia cell line - Zhang, Xiufen; Xie, Keming; Zou, Jian; Li, Yuling; Mu, Huijun; Zhang, Bin; Xie, Ping (Zhonghua yi xue yi chuan xue za zhi, 2014)
To investigate whether transcription factor-kappaB (NF-κ B) is involved in the modulation of P-glycoprotein (P-gp) by glucosylceramide synthase (GCS) in a multidrug resistance leukemia cell line K562/A02 and to explore the relationship between NF-κ B and extracelluar signal-regulated kinase (ERK). K562/A02 cells were treated with GCSsiRNA, pyrrolidine dithiocarbamate (PDTC, a NF-κ B specific inhibitor) and U0126 (a MEK1/2 inhibitor), respectively. The expression of GCS and multidrug resistance protein 1 (MDR1) mRNA were analyzed with qRT-PCR. Various proteins of different groups were measured by Western blotting. After transfected with GCSsiRNA for 48 h, GCS mRNA were reduced by 62% (51%-73%) and MDR1 mRNA was reduced by 52% (43%-61%) in the K562/A02 cells. Compared with the negative control, relative expression of NF-κ B p65 in nuclear and P-ERK1/2 were both down-regulated, and P-gp was also inhibited significantly at 72 h after transfected with GCSsiRNA (P< 0.05). In addition, the expression of P-gp was dec